PERAN KOMUNIKASI POLITIK PEMERINTAH DALAM MENCEGAH DISINTEGRASI BANGSA - Supriyatno, Yanto (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2010)
One of the functions of political communication is to give information from top to bottom or vice versa, and with this horizontal information system will produce a mutual understanding between the state/government and organizations that become their subordinate. Political communication is a tool in managing, coordinating and regulate state institutions vertically or horizontally